Reflection of Local Wisdom Values behind Accounting Practices in Tumbilotohe Culture - Thalib, Mohamad Anwar; Briando, Bobby (Invest Journal of Sharia & Economic Law, 2023)
This study explores the integration of local wisdom into accounting practices in the Tumbilotohe culture, framed within an Islamic paradigm and using an Islamic ethnomethodological approach. Data were collected through structured interviews, passive participant observation, and documentary analysis using a qualitative methodology. These were analyzed through the stages of charity, knowledge, faith, revelation information, and courtesy. The findings reveal that the Tumbilotohe Implementation Committee self-funded its activities through accounting practices that are deeply intertwined with values of sincerity, struggle, and sacrifice that are emblematic of the Gorontalo tribe's cultural and Islamic traditions. Central to these traditions is the vow "batanga pomaya, nyawa podungalo" (the self is devoted, life is at stake), which is part of the "Paduma" - five sacred agreements symbolizing the tribe's commitment to their land, including prioritizing religion, glorifying the land, devoting oneself to the land, sacrificing property, and risking life. The study concludes that accounting practices in the Tumbilotohe cultural celebration transcend mere financial transactions and are significantly influenced by local wisdom and religious values. This reflects the community's commitment to preserving their culture and embodying Paduma principles in organizing and defending their heritage, and provides a nuanced understanding of the role of cultural and religious values in shaping accounting practices in the Gorontalo community.